Motor Coordination Correlates with Academic Achievement and Cognitive Function in Children - Fernandes, Valter R.; Ribeiro, Michelle L. Scipião; Melo, Thais; de Tarso Maciel-Pinheiro, Paulo; Guimarães, Thiago T.; Araújo, Narahyana B.; Ribeiro, Sidarta; Deslandes, Andréa C. (Frontiers in Psychology, 2016)
The relationship between exercise and cognition is an important topic of research that only recently began to unravel. Here we set out to investigate the relation between motor skills, cognitive function and school performance in 45 students from 8 to 14 years of age. We used a cross-sectional design to evaluate motor coordination (Touch Test Disc), agility (Shuttle Run Speed - running back and forth), school performance (Academic Achievement Test), the Stroop test and 6 sub-tests of the Wechsler Intelligence Scale for Children-IV (WISC-IV). We found that the Touch Test Disc was the best predictor of school performance (R²=0.20). Significant correlations were also observed between motor coordination and several indices of cognitive function, such as the total score of the Academic Achievement Test (Spearman’s rho=0.536; p<=0.001), as well as two WISC-IV sub-tests: block design (R= -0.438;p=0.003) and cancellation (rho= -0.471; p=0.001). All the other cognitive variables pointed in the same direction, and even correlated with agility, but did not reach statistical significance. Altogether, the data indicate that visual motor coordination and visual selective attention, but not agility, may influence academic achievement and cognitive function. The results highlight the importance of investigating the correlation between physical skills and different aspects of cognition.